P-OGC11 Vitamin B12 supplementation post gastrectomy. A service audit in St. James's hospital, Dublin. (16th December 2021) - Temperley, Hugo; Murray, Cian; Carey, James; Bolger, Jarlath; Ravi, Narayanasamy; Reynolds, John V; Donohoe, Claire
Abstract: Background: Vitamin B12 deficiency is a well described complication post gastrectomy. It is caused by the loss of parietal cell mass leading to megaloblastic anaemia and possible long term neurological symptoms. Treatment can be with standardised replacement regimens or to monitor B12 levels and replace as required. This study assesses patient understanding of and compliance with B12 supplementation guidelines post total and subtotal gastrectomy. Methods: 125 patients who underwent gastrectomy between 2010-2020 were available for study (86 total gastrectomies, 39 subtotal gastrectomies). Patient data was collected by review of the hospital electronic records and individual phone calls. Patients were asked standardised questions to elicit knowledge of the importance of B12 supplementation and compliance with supplementation. Results: 92% (79/86) of total gastrectomy patients reported compliance in regular parenteral B12 supplementation. Compliance was significantly lower for subtotal gastrectomies for checking and/or replacing their vitamin B12 at 53.8% (21/39) (p < 0.001). 62.6% of patients stated that they knew it was important to supplement B12 post gastrectomy. 37.8% of participants could explain why this was important and 14.8% had any knowledge of the complications of vitamin B12 deficiency. Patients who were compliant with B12 supplementation had an improved understanding of why supplementation was important compared to those who did not. Conclusions: Regular monitoring and supplementation of vitamin B12 levels is important post gastrectomy. This study demonstrates good compliance in those undergoing total gastrectomy. Patient understanding correlates with compliance, suggesting that patient education and knowledge reinforcement may be key to compliance with vitamin B12 supplementation.